Proses Generalisasi Pola Bilangan Siswa SMP dalam Memecahkan Masalah Matematika Berdasarkan Gaya Belajar - Andi Mulawakkan Firdaus; Irwan Akib; Nasrun . (Universitas Islam Jember, 2022)
This study aims to describe the process of generalizing number patterns in solving mathematical problems based on visual, auditory and kinesthetic learning styles. The subjects in this study were three grade VIII students of SMP Muhammadiyah Limbung with visual, auditory and kinesthetic learning styles. Data collection was done by giving a learning style questionare and a generalization test of patterns and interviews. This research is a qualitative research. The data were analyzed by means of descriptive and classification. The results showed that research subjects who had visual learning styles were able to perform better problem-solving stages than audio and kinesthetic learning styles. This is because the visual learning style has the nature of reading or understanding written instructions which results in the visual learning style being able to code and process information well and regularly. Keywords: generalization process, number patterns, learning styles